Korelasi Disiplin Belajar dan Aktivitas Belajar pada Pembelajaran Tematik dengan Hasil Belajar Siswa Kelas V Sekolah Dasar Negeri 29 Pontianak Kota - Iksan Iksan; Siti halidjah; Dyoty Auliya Vilda Ghasya (Journal on Education, 2023)
This study aims to describe the correlation between learning discipline, learning activities and student learning outcomes in thematic learning class V SD Negeri 29 Pontianak kota. The method used in this research is descriptive in the form of a correlation study. The population of this study were all fifth grade students at SD Negeri 29 Pontianak Kota, totaling 29 students. Sampling was carried out using purposive sampling with a sample of 29 fifth grade students at SD Negeri 36 Pontianak Selatan. Data collection techniques use indirect communication to collect data on learning disciplines, learning activities and documentary study techniques for learning outcomes. The collection tool is a questionnaire. Data analysis technique uses Product moment. The correlation between learning discipline and learning outcomes is 0.440, between learning activities and learning outcomes is 1.405, and between learning disciplines and learning activities with learning outcomes is 1.406, in the high category. rtable of 0.367 with a significance level of 5%, then 1.406 <0.367. So it can be concluded that Ho is rejected and Ha is accepted because there is a correlation between learning discipline and learning activities with student learning outcomes in class V SD Negeri 29 Pontianak Kota